Parent Preferences for Neonatal Intensive Care Unit Physician Attire: A Cross-Sectional Study - Cham, Parul; Laventhal, Naomi; Burrows, Heather; Chopra, Vineet; Weiner, Gary M. (American Journal of Perinatology, 2021)
Objective Physician attire may influence the parent-provider relationship. Previous studies in adult and outpatient pediatrics showed that formal attire with a white coat was preferred. We aimed to describe parent preferences for physician attire in the neonatal intensive care unit (NICU).Study Design We surveyed 101 parents in a level IV NICU. The survey included photographs of a physician in seven different attires. Attire was scored in five domains and parents selected the most preferred attire in different contexts. All attires were compared with formal attire with white coat. Descriptive statistics, Fisher's exact tests, and one-way analysis of variance were used to compare parent responses.Results Scrubs without white coat (40.8 [7.0]) and formal attire without white coat (39.7 [8.0]) had the highest mean (standard deviation) composite preference scores. However, no significant differences between formal attire with white coat (37.1 [9.0]) versus any other attire were observed. When asked to choose a single most preferred attire, scrubs with a coat (32%) and formal with a coat (32%) were chosen most often, but preferences varied by clinical context and parent age. For example, parents preferred surgical scrubs for physicians performing procedures. Parents indicated that physician attire is important to them but does not influence their satisfaction with care.Conclusion Although parents generally favored formal attire and scrubs, the variations based on the context of care and lack of significant preference of one attire suggests that a single dress code policy for physicians in a NICU is unlikely to improve the patient-provider relationship.Key Points
Keywords: neonatal intensive care unit; physician attire; patient preference; physician and patient relations